On the Role of Poroelasticity in the Propagation Mode of Natural Fractures in Reservoir Rocks - Kamali, Amirhossein; Ghassemi, Ahmad (Rock mechanics and rock engineering, 2020)
Almost all reservoir rocks contain natural fractures. The presence of such discontinuities affects reservoir stimulation to a certain degree. The interaction between the natural and hydraulic fractures determines the overall fracture trajectory and the stimulated reservoir volume. In contrast to conventional hydraulic fracturing, natural fractures do not propagate in a tensile-dominated regime. Propagation of mechanically closed fractures lies in the mixed-mode propagation regime which differs from that of open fractures. Therefore, the response of natural fractures to pore pressure and stress perturbations should be carefully addressed within the context of reservoir stimulation. This study aims at investigating the response of closed natural fractures to water injection in poroelastic rocks. A poroelastic displacement discontinuity (DD) model is developed and used to shed light on the propagation of closed natural fractures. Mohr–Coulomb contact elements are used in this study to identify the contact status of the elements in the transverse direction. Moreover, fracture propagation is effectively accounted for based on linear elastic fracture mechanics. Hydro-mechanical coupling is achieved by combining an implicit finite difference scheme with the poroelastic DD model. Our simulation results indicate that natural fracture shear slip and propagation are likely to occur when the closed natural fractures are subject to direct water injection. The injection pressure required to maintain the propagation in poroelastic rocks was found to be consistently higher than the pressure in its elastic counterpart. The propagation trajectory of the wing cracks was, on the other hand, found to be similar to that in elastic rocks. It was found in our results that the formation of wing cracks and shear (secondary) cracks is an integral part of the reservoir stimulation in geothermal systems where natural fractures are in direct contact with the injection wells. This point is often overlooked or poorly treated and has led to erroneous interpretations from the reservoir stimulation standpoint.